PENGARUH CAMPURAN MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Agustinus Danga Ate; I Putu Sujana; Komang Dean Ananda; Luh Putu Yuni Widyastuti; Bagus Putu Udiyana (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This study entitled the effect of a mixture of planting media on the growth and yield of land kangkung (Ipomoea reptans Poir). The effect of organic fertilizer is treated to increase growth and yield. The purpose of this study was to analyze the effect of the type of planting medium on the growth and yield of land kangkung and to analyze gave the best growth and yield using cow manure, goat manure, chicken manure, vermicompost fertilizer, and mixed fertilizers (cow cage, goat cage, chicken manure, and vermicompost). with 6 levels K0 (without fertilizer), K1 (cow manure 50 g / 10 kg soil), K2 (goat manure 50 g / 10 kg soil), K3 (chicken manure 50 g / 10 kg soil), K4 (vermicompost 50 g / 10 kg soil), and K5 (mixed fertilizer 50 g / 10 kg soil). In the results of this study, all parameters gave good results, and for planting media the best results were using mixed manure 10 tons/ha or 50 g/10 kg of soil polybag for all observed parameters. The application of mixed fertilizer on land kangkung gave a plant height of 4 WAP which was 43.00 cm, the number of leaves was 25.50 cm, leaf area was 641.69 cm, the total fresh weight of the plant was 90.25 g, the fresh weight of the above-ground plant was 72.88 g, the dry weight of the above-ground plant was 7.51 g, and the total oven-dry weight of the plant was 11.55 g.